Students’ Perceptions Toward Quizizz as An Assessment Tool in EFL Classroom - Rafida Aulia; Silih Warni (International Journal of Research in Education, 2024)
This study employs a descriptive qualitative approach to describe the implementation of Quizizz and identify the students’ view toward Quizizz as an assessment tool in EFL classrooms. Eight second-year students are participated and selected based on their prior use of Quizizz during English lessons. Data collection involved classroom observations and in-depth interviews.  The data were collected, transcribed, and analyzed thematically. The findings indicate that Quizizz is effectively employed by teachers, eliciting active engagement from students who appreciate its gamified features. Four key themes emerged from the analysis: Interest in Quizizz, Motivation in Quizizz, Confidence in Quizizz, and English Skills in Quizizz. Participants expressed enthusiasm for Quizizz's gamified learning approach and its integration of technology, which they perceived as enhancing teachers' assessment capabilities. They also noted that Quizizz served as a motivational tool, boosting their confidence and improving their English skills, notably in vocabulary acquisition and reading comprehension. Overall, Quizizz emerged as an effective and enjoyable tool for enhancing student engagement and facilitating learning outcomes in English. For educators, integrating Quizizz into lesson plans proves to be an efficient method for fostering student involvement and evaluating learning achievements.